PERSONS WITH DISABILITIES IN PAKISTAN - Arsh, Aatik; Darain, Haider (Annals of Allied Health Sciences, 2019)
The plights and miseries of persons with disabilities (PWDs) have been highlighted and discussed since the inception of Pakistan; however, no concrete measures have been taken for the rights of PWDs. According to World Health Organization (WHO), about 15% of the world’s population live with some sort of disability. Nevertheless, according to 1998 census only 2.49% and according to 2017 census only 0.48% of the population had disability in Pakistan. Moreover, only 136,928 PWD’s has been issued national identity cards and may be regarded registered PWDs in the country. Though disability is more prevalent in developing countries as compared to developed countries and poverty, illiteracy, natural disasters and continuous exposure to armed conflicts predispose people to disability, yet the lower number of reported PWD’s in Pakistan clearly shows that there is huge discrepancy in the reported statistics. The ground reality is that, these figures are just assumption and because of under reporting of disability there are thousands of PWD’s which are not registered and the fact is that, the exact figure of PWD’s is much higher than this. If we even don’t know exact number of PWD’s, so how can we plan to address issues related PWD’s. Scarcity of reliable disability epidemiologic data is one of the major barrier in addressing issues related to PWD’s in Pakistan. The words “Disable” and “Disability” are often used in negative sense in Pakistani society. PWD’s are never accepted in society and they are often disregarded and mistreated. Because there are limited opportunities of education and employment for these PWD’s, majority of PWD’s live a dependent life. In Pakistan, due to lack of facilities, mostly PWD’s are unable to continue their education and therefore unable to get higher degrees which is main hindrance in getting high level posts. But the truth is that in majority of cases even highly qualified PWD’s are deprived of job opportunities. Majority of people living in community are unaware of the capabilities of PWD’s and that’s why administrators are usually hesitant to employ PWD’s as they have reservations that PWD’s might not be able to carry out their duties efficiently. There are reports that due to the fear that hiring of PWD’s may affect output, employers prefer to pay fine rather than hiring PWD’s. Another important barrier to employment of PWD’s in Pakistan is that majority of places including government departments in country are not wheel chair accessible. Similarly, public transport is also not accessible to PWD’s. Negative attitude and superstitious beliefs towards PWD’s is reported by many research studies and is evident throughout history. Though many studies conducted in Pakistan, reported social rejection of PWD’s in country and truth is that problems of PWD’s are much more than that yet due to religious affiliations, general population living in Pakistan demonstrate strong afflation’s towards PWD’s. Islamic teachings focuses on the fact that it is the responsibility of government as well as of society to support PWD’s and provide equivalent opportunities of learning and employment to PWD’s. In order to protect rights of PWD’s and to make them functional members of society, Government of Pakistan provide many constitutional and legal provisions to PWD’s living in Pakistan. The most important national policy in this regard is fixed job quota for PWD’s in both government and private sector. In 1981, ex-president of Pakistan Zia-ul-Haq, allocated 1% job quota for PWD’s through ordinance “Disabled Persons (Employment and Rehabilitation) Ordinance (DPO-1981)" while in 1998Prime minister Pakistan Nawaz Sharif increased PWD’s job quota from 1% to 2%. The present job quota for PWD’s in all provinces of Pakistan is 2% except Punjab where the quota was raised to 3% in 2015. National policy for PWD’s (2002) clearly mentioned that “Pakistan joined the select group of countries, which has not only ratified ILO Convention 159, but have also taken active legal steps to introduce legislation which lays down quota for the employment of persons with disabilities”. It is further added that, “The penalty clauses will also be amended to make its implementation more effective”. Section 11 of The Disabled Persons (Employment and Rehabilitation) Ordinance, 1981 also emphasizes that “An establishment which does not employ a disabled person shall pay in to the Funds each month the sum of money it would have paid as salary or wages to a disabled person had he been employed”. Keeping in view the fact, that 2% quota for PWD’s is not following in Pakistan, Aisha Syed, member of National Assembly of Pakistan presented “The Disabled Persons (Employment) and Rehabilitation (Amendment) Act 2015” in National Assembly in order to strengthen the rights of PWD’s in Pakistan. The said bill emphasizes that serious action to be taken against departments which ignores 2% quota of PWD’s. To sum up, it can be concluded that despite the fact that a number of national policies exist regarding legal rights of PWD’s in the country, PWD’s are still deprived of their rights in Pakistan. They remained marginalized part of society and they are almost always neglected and ignored in the community. The main reason behind it is that these policies are only present in papers and never implemented. These policies are useless until and unless they are implemented with true spirit.